An ultra-high strength martensitic steel fabricated using selective laser melting additive manufacturing: Densification, microstructure, and mechanical properties. (March 2020) - Seede, Raiyan; Shoukr, David; Zhang, Bing; Whitt, Austin; Gibbons, Sean; Flater, Philip; Elwany, Alaa; Arroyave, Raymundo; Karaman, Ibrahim
Abstract: Martensitic steels have gained renewed interest recently for their use in automotive, aerospace, and defense applications due to their ultra-high yield strengths and reasonable ductility. A recently discovered low alloy martensitic steel, AF9628, has been shown to exhibit strengths greater than 1.5 GPa with more than 10% tensile ductility, due to the formation of ε-carbide phase. In an effort to produce high strength parts with a high degree of control over geometry, the work herein presents the effects of selective laser melting (SLM) parameters on the microstructure and mechanical properties of this new steel. An optimization framework to determine the process parameters for building porosity-free parts is introduced. This framework utilizes the computationally inexpensive Eagar-Tsai model, calibrated with single track experiments, to predict the melt pool geometry. A geometric criterion for determining maximum allowable hatch spacing is also developed in order to avoid lack of fusion induced porosity in the as-printed parts. Using this framework, fully dense samples were successfully fabricated over a wide range of process parameters, allowing the construction of an SLM processing map for AF9628. The as-printed samples displayed tensile strengths of up to 1.4 GPa, the highest reported to date for any 3D printed alloy, with up to 11% elongation. The demonstrated flexibility in process parameter selection, while maintaining full density, opens up the possibility of local microstructural refinement and parameter optimization for improved mechanical properties in as-printed parts. The process optimization framework introduced here is expected to allow successful printing of new materials in an accelerated fashion. Graphical abstract: Image, graphical abstract